Henryk Skolimowski’s critique of western civilization in the context of the ecological crisis - Czekalski, Rafał (Studia Ecologiae et Bioethicae, 2014)
In this article, the authors look at the topic of the crisis of Western civilization in the context of the ecological crisis. In the opinion of a Polish ecophilosopher, the latter is a symptom of the failure of a scientific-technological civilization, which Skolimowski often contemptuously calls plastic. In the first part, the authors present Skolimowski's diagnosis of Western civilization, in the second part they describe the postulate of a new ecological civilization. The Polish ecophilosopher is aware of the fact that this requires a new look at philosophy itself, a new science, new ethics, a new education, and even a new ecological spirituality. The recurring adjective 'new' points on the one hand to the necessity of breaking with current philosophical tradition and on the other – to opening up to and looking for inspiration in present existential dimensions; this referring mainly to broadly understood spirituality. In the last part of the article, the authors take a critical look at H. Skolimowski's civilizational project, at the same time holding in great regard his work and his engagement in relation to environmental protection.